The life of Sir William Fairbairn, Bart., F.R.S., LL.D., D.C.L., ... - Fairbairn, William, Sir, 1789-1874 (Longmans, Green, 1877)
After preliminary chapters on the engineering profession this biography covers: Fairbairn's childhood, first employment and apprenticeship; his moves to and work in London and Manchester; his work on water-wheels, canal transportation, and iron ship-building; his work for the Turkish government; his work on the Conway, Britannia, and Rhine bridges; his scientific honours and literary work.